2019
DOI: 10.1007/s11239-019-01934-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with under-dosing of rivaroxaban for management of non-valvular atrial fibrillation in real-world Japanese clinical settings

Abstract: The approved dose of oral anticoagulant rivaroxaban for patients with non-valvular atrial fibrillation (NVAF) in Japan is 15 mg once daily (od) in patients whose creatinine clearance is ≥ 50 mL/min, but recent real-world studies have demonstrated that these patients often received less than the recommended dose due to bleeding concerns. The effect of under-dosing on safety and effectiveness outcomes remains unclear. We used 1-year follow-up data from the XAPASS, a real-world Japanese prospective, single-arm, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 19 publications
7
50
1
1
Order By: Relevance
“…Reduced dosing of NOACs is a pertinent clinical concern as it may impact the safety and/or effectiveness of treatment 18 31 32. In the current study, risks for bleeding and stroke/SE were generally consistent between the standard-dose and reduced-dose NOAC subgroups, and we observed a significantly lower risk of stroke/SE with reduced-dose apixaban versus warfarin.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Reduced dosing of NOACs is a pertinent clinical concern as it may impact the safety and/or effectiveness of treatment 18 31 32. In the current study, risks for bleeding and stroke/SE were generally consistent between the standard-dose and reduced-dose NOAC subgroups, and we observed a significantly lower risk of stroke/SE with reduced-dose apixaban versus warfarin.…”
Section: Discussionsupporting
confidence: 65%
“…Broadly, these real-world results provide supportive evidence for the existing RCTs that have demonstrated the clinical benefits of NOACs versus warfarin in patients with NVAF 6–10. Moreover, the current study builds on the emerging, real-world evidence base for the effectiveness and safety of NOACs in Japanese clinical practice 15–18 30…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Under‐dosing of DOAC has been reported in many studies. Some studies reported higher thromboembolic events in nonrecommended lower‐dosed patients than in patients with the recommended dose, and others found no significant differences in clinical outcomes between the two patient groups 20,27‐30 . In this study, 11.4% of patients were receiving a nonrecommended lower‐dose, and physicians might have chosen the dose because of advanced age or renal dysfunction and were considered to be at a higher risk of bleeding.…”
Section: Discussionmentioning
confidence: 54%
“…Outcomes associated with the underdosing of rivaroxaban have been reported elsewhere. 17 Baseline characteristics of patients included in this subanalysis were similar to those of patients who completed 1-year follow-up. 15 Concomitant use of antiplatelets was predictive of both stroke/non-CNS SE/MI and major bleeding, whereas a history of ischemic stroke/ TIA and age greater than or equal to 75 years were predictors of stroke/non-CNS SE/MI only, and renal impairment (CrCl <50 mL/min) and diabetes were predictors of major bleeding only.…”
Section: Discussionmentioning
confidence: 84%